System Implementation Optimization Stollen Recovery Initiative (StAR) as an Effort to Eradicate Criminal Corruption in Asia - Fairuza, Hanny Hilmia; Dewi Rastikasari; Desi Nur Fitria; Nesya Wahyuning Asep Saputri (JURNAL RUANG HUKUM, 2022)
Corruption is a form of criminal behavior that is detrimental to state finances. Acts of corruption do not only occur in one country, but also in all countries, especially ASEAN. Therefore, it is necessary to carry out cooperation in the international sphere through an agreement or the implementation of political cooperation in the form ofMutual Legal Assistance (MLA) andExtradition related to the eradication of corruption. There are UN conventions andMLA will provide a form of change in the form of a paradigm related to the many aspects of corruption as a form of crimeinternational-transnational. In this case it becomes one of the important factors for all countries in achieving efforts to combat corruption. With regard to efforts to eradicate criminal acts of corruption, it is necessary to have a special regulatory system related to the handling of acts of corruption in foreign relations, one of which is in the form ofStollen Asset Recovery Initiative or StAR. StAR is a form of international cooperation in terms of providing evidence and transparency of an act of corruption.